Experimental validation of a theoretical model for flexural modulus of elasticity of thin cement composite - Hossain, M.Z.; Abdul Awal, A.S.M. (Elsevier, 2011)
Experimental and analytical investigations for the modulus of elasticity of thin cement composite composed of mesh and mortar are demonstrated. Based on the analyses and experimental data, new equations for the modulus of elasticity of thin cement composite are proposed. It is observed that the flexural modulus of elasticity of thin cement composite depends on the elastic modulus of mortar and some factor of the difference of elastic modulus of mesh and mortar. Results obtained by using the proposed equations are compared to those of the available equations. It has been found that the newly developed equations give relatively conservative results as compared to the typically used ones. A comparison between the analytical and experimental findings further indicates that there is a good agreement between the analytical and experimental results